Influence of Interactive Media-based Kahoots Application with Islamic Questions on Students’ Learning Outcomes - Faiq Alwan Fauzan Faiq; Ishaq Nuriadin Ishaq (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
Learning mathematics has a very important role in forming the attitudes and mindsets of students and solving problems independently. The problems faced at this time are that students have low mathematics learning outcomes and students feel the material they are learning is difficult, and the way of learning in learning mathematics is less effective. The teacher is still the center of the learning and teaching process of mathematics. Therefore, this study aims to determine the effect of Kahoot learning media on the mathematics learning outcomes of fifth-grade students at MI Unwanul Huda. The Kahoot application media is interactive and interesting, so students don't feel bored and bored in learning. This application is a game in the form of a test. The method used in this study is a quantitative experimental method in the form of a quasi-experimental design with one group pretest and posttest design. Sampling was done by the saturated sampling technique. The sample of this study consisted of a class, namely class V, which consisted of 28 students. The data collection technique used is the test. The results of the hypothesis test used the t-test with parametric statistics. It is known that the average post-test of student learning outcomes using Kahoot learning media is 65.00 and the average pre-test of student learning outcomes is 37.14. So it can be concluded that there is an influence on the mathematics learning outcomes of students who use Kahoot learning media.